Contact heat and cold, mechanical, electrical and chemical stimuli to elicit small fiber-evoked potentials: Merits and limitations for basic science and clinical use - Baumgärtner, Ulf; Greffrath, Wolfgang; Treede, Rolf-Detlef (Neurophysiologie clinique, 2012)
Summary: Laser-evoked potentials are the most extensively validated method to objectively assess nociceptive pathway function in humans. Here, we review merits and shortcomings of alternative techniques using different principles of stimulus generation to stimulate Aδ- or C-fibers. Fast ramp contact heat stimuli yield reproducible responses; however, stimulus location needs to be changed to reduce peripheral habituation, and the limited steepness of temperature ramps may result in response jitter and absence of averaged responses even in some healthy subjects. Inverse temperature ramps can serve to evoke cool evoked potentials to specifically test the cold pathway; the clinical impact of such findings is promising but uncertain to date, and availability of devices optimized for this purpose is currently limited. Mechanical stimuli excite low- or high-threshold mechanoreceptors depending on both the probe surface and the applied force. Electrical stimuli can be used to excite nerve fibers directly in the epidermis, the mucosa of the gut, or the tooth pulp. Principle limitation of the applicability of mechanical and electrical stimuli is the inevitable co-excitation of tactile (Aβ−) fibers. The nasal mucosa can be stimulated using pulsed-CO2 air streams, which excite chemo-nociceptors; although these stimuli are specific to excite thin trigeminal afferents, their use is limited as it is restricted to a relatively small region. Current data do not allow a comparative analysis on their respective diagnostic values. Quantification of analgesic efficacy in healthy subjects has been established and may be useful in phase I and IIa clinical trials. Résumé: Les potentiels évoqués au laser constituent la méthode actuellement la mieux validée pour l’étude objective du système nociceptif humain. Dans cet article, nous passerons en revue les avantages et inconvénients d’autres techniques basées sur différentes méthodes de stimulation destinées à stimuler les fibres myélinisées de fin calibre de type Aδ ou les fibres non myélinisées de type C. Des réponses reproductibles peuvent être obtenues au moyen de rampes d’échauffement rapide. Cependant, le site de stimulation doit être continuellement modifié pour éviter l’habituation et une limitation de la pente de la rampe d’échauffement peut entraîner une variabilité des réponses, voire l’absence de réponses moyennées même chez les sujets normaux. Inversement, des rampes de refroidissement peuvent être utilisées en vue de l’étude des voies nerveuses spécifiques du froid. L’impact clinique de ces techniques prometteuses reste actuellement incertain et la disponibilité des systèmes de stimulation est encore très limitée. En fonction de leur surface d’application et de la force exercée, des stimuli mécaniques peuvent exciter des mécanorécepteurs à seuils élevés ou bas. Des stimulations électriques peuvent être utilisées pour exciter directement les fibres nerveuses de l’épiderme, de la muqueuse intestinale ou de la pulpe dentaire. La co-activation des fibres tactiles Aβ constitue la limitation majeure des stimuli électriques et mécaniques. Les chémorécepteurs de la muqueuse nasale peuvent être directement excités au moyen de bouffées d’air pulsé contenant de hautes concentrations de CO2. Bien que ces stimuli soient spécifiques des fibres trigéminées afférentes de fin calibre, leur principale limitation est de ne concerner qu’une région très restreinte. Les données actuellement disponibles ne permettent aucune comparaison de leurs valeurs diagnostiques respectives. On sait maintenant qu’il est possible d’utiliser ces méthodes pour quantifier l’efficacité de méthodes analgésiques chez des sujets normaux, justifiant leur utilité dans les essais cliniques en Phase I et IIa.